Emotions, Metacognition, and the Intuition of Language Normativity Theoretical, Epistemological, and Historical Perspectives on Linguistic Feeling - Romand, David; Le Du, Michel (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XIII, 367 p. 2 illus.